What is new in lipid‐lowering therapies in diabetes?. Issue 12 (5th December 2019) - Cheung, Yee‐Ming; O'Brien, Richard; Ekinci, Elif I.
Abstract: Diabetes can lead to a myriad of microvascular and macrovascular complications – with the leading cause of mortality in diabetes being cardiovascular disease. Low‐density lipoprotein cholesterol, along with non‐high‐density lipoprotein cholesterol and triglycerides are proven, modifiable risk factors for cardiovascular disease. This article will focus on lipid‐lowering agents in individuals with diabetes. It will summarise relevant changes in the latest guidelines for dyslipidaemia and will also review the mechanisms of action of lipid‐lowering agents along with the latest cardiovascular outcomes data specific to individuals with diabetes. Older agents such as statins, ezetimibe, fibrates and nicotinic acid will be reviewed with a focus on new diabetes‐specific evidence. Similarly, a relatively novel agent proprotein‐convertase subtilisin‐kexin type 9 will be reviewed and details around the Pharmaceutical Benefits Scheme criteria governing its usage in Australia will be reported. Finally, this review will touch on agents still on the horizon such as icosapent ethyl, high‐density lipoprotein mimetics, bempedoic acid, omega‐3 free fatty acids, bromodomain and extra‐terminal protein inhibitors and inclisiran – a long‐acting ribonucleic acid interference agent. In the appropriately selected population of individuals with diabetes, these agents can assist to improve further lipid profile and reduce cardiovascular events.